The wizardry of Id [video games]. - Kushner, D. (IEEE spectrum)
The author takes a look at some of the technology that helped make the video games industry as big as Hollywood. Through its technologically innovative games, Id Software has had a huge influence on everyday computing, from the high-speed, high-color, and high-resolution graphics cards common in today's PCs to the marshalling of an army of on-line game programmers and players who have helped shape popular culture.